Prognostic value of the six-minute walk test in patients with cardiovascular disease - Sangho Sohn; Jinsung Jeon; Ji Eun Lee; Soo Hyung Park; Dong Oh Kang; Eun Jin Park; Dae-In Lee; Jah Yeon Choi; Seung Young Roh; Jin Oh Na; Cheol Ung Choi; Jin Won Kim; et al. (Scientific Reports)
Abstract The six-minute walk test (6MWT) is a convenient method for evaluating functional capacity in daily living. We evaluated the prognostic value of the 6MWT in patients with cardiovascular disease to predict the incidence of MACE. Patients with prevalent cardiovascular diseases were enrolled in the cardiac rehabilitation registry. 6MWT was measured at baseline, and incidences of all-cause death, coronary intervention, admission due to heart failure, and stroke were monitored. Odds ratios (OR) and hazard ratios (HR) for MACE were compared, and cutoff distance of 6MWT according to endpoint diseases were calculated for both common and disease-specific thresholds. A total of 1,374 patients were enrolled, with 105 (7.6%) MACE events. The MACE group walked shorter 6MWT distances (329 ± 110 m) compared to controls (396 ± 114 m, p < 0.001). Each 50-meter increase in 6MWT distance was associated with a lower OR (0.78, p < 0.001) and HR (0.83, p < 0.001) for the MACE. Cutoff distance for MACE was 392 m, with sensitivity of 76% and specificity of 53%. The disease-specific cutoffs provided better classification of individual outcomes for all-cause death, coronary intervention, and stroke. The 6MWT has a prognostic value for predicting MACE in patients with prevalent cardiovascular diseases. Different thresholds should be applied for specific diseases to enhance the predictive accuracy.